Sorptivity of an Inceptisol under Conventional and Reduced Tillage Practices - Rachman, Achmad; Ariani, Ratri; Budiyanto, Arief (JOURNAL OF TROPICAL SOILS, 2017)
The amount of water captured and stored in the soil profile until the next precipitation events is of great importance in dryland agro-ecosystem for successful crop production. The soil’s ability to rapidly capture and store water precipitation can be accessed through measuring soil sorptivity. The objectives of this study were to evaluate the effects of tillage, i.e. reduced and conventional tillages, on soil sorptivity, and to understand how sorptivity is related to surface soil bulk density and water stable aggregates. The experiment was conducted on a site, which has been continuously planted with corn twice a year for more than 10 years.  The predominant soil in the study site is Typic Haplusteps. Ponded infiltration measurements were used to determine soil sorptivity.  Six positions, 15 meters a part, were chosen within each treatment to measure sorptivity, bulk density and water stable aggregates.  Conventional tillage resulted in higher sorptivity (p<0.05), lower surface bulk density (p<0.05), and significantly lower water stable aggregates (p<0.01) than reduced tillage treatment. Sorptivity was negatively correlated to bulk density and positively correlated to water stable aggregates. Better correlations were found between sorptivity and both bulk density (R2 = 0.67) and water stable aggregates (R2= 0.81) under reduced tillage than under conventional tillage treatment.  Conventional tillage was found to enhance soil sorptivity in comparison to reduced tillage system. Appropriate soil management is important to maintain proper soil porosity in the field for better rainfall harvesting and plant growth especially in the dryland ecosystem.